La dramatización como técnica para elevar la autoestima de las niñas y niños de primer grado de la escuela de educación básica Alonso de Mercadillo de la ciudad de Loja. Período 2014-2015 - Quezada Soto, Mirian Andrea (2016)
The present research project titled The drama as a technique to raise the self-esteem of children from first grade Alonso of Mercadillo Elementary School of Loja City. Period 2014-2015; The overall objective is to highlight the importance of drama techniques to enhance the self-esteem in children of first-degree methods were used: scientific, analytical, synthetic, inductive,deductive and descriptive; the same which facilitated the schematic development of research and the comparison of data, as techniques were applied the the observation, surveys to 5 first grade teachers, in order to know the importance given to dramatization techniques to raise self-esteem . To assess children it was made an observation guide based in the curriculum education and test self-esteem of Lewis R Aiken which was applied to 30 children, the same was used to explore the opinion that each child on himself, his image. It may show that 100% of the answers rated the importance of drama techniques, That is to say that it is connected to various strategies and stimulations that help to improve the self-esteem. It is recommended that the institution continue implementing these techniques, since thus children will be encouraged to bring out their learning skills in different fields of adaptation.